Advances in Microfluidics Applied to Single Cell Operation. Issue 2 (19th January 2018) - Zhu, Xu‐Dong; Chu, Ju; Wang, Yong‐Hong
Abstract : The field of microbiology have traditionally been concerned with and focused on studies at the population level. Microfluidic platforms have emerged as important tools for biology research at a small scale, even down to a single cell level. The spatial and temporal control of cells and stimuli transported by microfluidic channels in well‐designed microsystems realized the studies of specific cells in a controlled microenvironment. The true cellular physiology responses, which are obtained mostly by inference from population‐level data, could be revealed in this way. Nowadays, significant applications like cell culture, analysis, sorting, genomics, and proteomics at the single cell level have been achieved in microfluidic chips. Highly integrated microfluidic systems with complete bio‐analytic functions are also coming forth and of great promise for single cell related physiology, biomedical, and high throughput screening research. Herein, the leads of technologies applied to single cell operation are reviewed. Challenges and potentials of these works are also summarized, to highlight fields for further research. Abstract : Microfluidic platforms have emerged as important tools for biology research at a small scale, even down to a single cell level. Significant applications like cell culture, analysis, sorting, genomics, and proteomics at the single cell level have been achieved in microfluidic chips. Highly integrated microfluidic systems with complete bio‐analytic functions are also coming forth and of great promise for single cell related physiology, biomedical, and high throughput screening research. Herein, the leads of technologies applied to single cell operation are reviewed.